Expression pattern of soluble triggering receptor expressed on myeloid cells-1 in mice with Acinetobacter baumannii colonization and infection in the lung - Hu, Chengping (J Thorac Dis, 2018)
BACKGROUND: Acinetobacter baumannii (A. baumannii) is one of the most troublesome opportunistic pathogens associated with hospital-acquired pneumonia (HAP). It is important to be able to discriminate A. baumannii colonization from infection in its early stages so that effective antibiotics can be promptly applied. Recent studies have reported that the secretion of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) is markedly upregulated in pneumonia and sepsis, but the expression pattern of sTREM-1 in A. baumannii colonization and infection in the lung has not been explored. METHODS: C57BL/6J male mice were intraperitoneally injected with 1% streptozotocin for 5 consecutive days to establish diabetic models. Subsequently, aerosol inhalation of A. baumannii suspension was performed in these mice to induce pulmonary colonization or infection with saline as vehicle control. Mice were sacrificed and lung tissue was harvested on days 0, 1, 3, 5 and 7 after exposure. Pharyngeal swab culture, lung homogenate culture, and H&E staining of lung tissue were performed to assess the severity of infectious inflammation. sTREM-1 expressions in serum and lung supernatants, serum procalcitonin (PCT) and C-reactive protein (CRP) concentrations were measured by ELISA. RESULTS: A. baumannii colonization and infection models were verified by pharyngeal swab culture, lung homogenate culture, and H&E staining. While sTREM-1 concentrations in mice with A. baumannii colonization remained unchanged in serum and lung supernatants, sTREM-1 expression levels in infected animals were significantly upregulated. In addition, serum sTREM-1 concentration was positively correlated with serum levels of PCT and CRP. CONCLUSIONS: Dynamic secretion of sTREM-1 is associated with the development of A. baumannii infection in the lung. Therefore, sTREM-1 expression level may be a promising biomarker for discriminating A. baumannii infection from colonization.